2008
DOI: 10.1080/07399330802269683
|View full text |Cite
|
Sign up to set email alerts
|

“You Really Do Something Useful with Kids”: Mothering and Experienced Health and Illness in a Group of Elderly Swedish Women

Abstract: This article is based on in-dept interviews with 20 elderly Swedish women, and deals with mother's child-caring work and related health and illness. Mothering included invisible work as well as physically heavy tasks, both aspects often neglected in research. The attitude of the children's father had a great impact on the work. Feelings of success or failure at bringing up their children affected the women's experience of health/ill health throughout their lives. Their health as elderly women depended on the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…IADL occupations within the maternal role were identified in 12 of the 14 articles. The focus in these studies was on the support older mothers give their adult children [ 32 , 34 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. The IADL occupations included assisting children with cooking or shopping, running errands for the children, tending their home, providing them with financial support, and caring for the grandchildren.…”
Section: Resultsmentioning
confidence: 99%
“…IADL occupations within the maternal role were identified in 12 of the 14 articles. The focus in these studies was on the support older mothers give their adult children [ 32 , 34 , 36 , 38 , 39 , 40 , 41 , 42 , 43 ]. The IADL occupations included assisting children with cooking or shopping, running errands for the children, tending their home, providing them with financial support, and caring for the grandchildren.…”
Section: Resultsmentioning
confidence: 99%
“…Feelings of success at raising their children were essential to mothers’ self-esteem and well-being even in old age (Heidrich, 1998; Kasle, Wilhelm, & Reed, 2002). This also applied to the women involved in the present study (Forssén & Carlstedt, 2008).…”
Section: Women’s Long-term Memories Of Childbirthmentioning
confidence: 99%
“…The importance of child-care support in the prevention of a mother's child care-related stress has been documented (Shaw et al, 2006). The primary caregivers of children are often mothers whose feelings of success or failure over bringing up a child affect their health (Forssén & Carlstedt, 2008). However, it has been reported that a high proportion of Japanese mothers was not confident of their child rearing (Goto et al, 2008) and that mothers with higher child-rearing anxiety had less social support in Japan (Arimoto & Murashima, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…, 2006). The primary caregivers of children are often mothers whose feelings of success or failure over bringing up a child affect their health (Forssén & Carlstedt, 2008). However, it has been reported that a high proportion of Japanese mothers was not confident of their child rearing (Goto et al.…”
Section: Introductionmentioning
confidence: 99%